Quantification of Chaoborus and small fish by mobile upward-looking echosounding - Roman Baran; Michal Tušer; Helge Balk; Petr Blabolil; Martin Čech; Vladislav Draštík; Jaroslava Frouzova; Tomáš Jůza; Jan Kubecka (Journal of Limnology, 2018)
Chaoborus larvae inhabit frequently the water column of lakes, when they can be mistaken for small fish. Because larvae ascend up to the blind zone of downward-looking echo sounding at night, quantitative acoustic estimation of them is possible only with upward-looking approach. For this reason, the mobile hydroacoustic upward-looking system (120 and 38 kHz split-beam echosounder) in combination with a direct catch method (trawling) was tested to investigate the night community of invertebrates and juvenile fish in the surface layer of the Římov reservoir (Czech Republic). In the target strength range of invertebrates (smaller than -59 dB), the 38 kHz echosounder recorded only a small proportion of targets while the 120 kHz echosounder recorded distinct peaks corresponding to high densities of Chaoborus (target strength, TS range -70 to -60 dB, average TS -66 to -64 dB). At 120 kHz frequency, the TS distribution of smaller cohort of juvenile fish (<25 mm in length) overlapped the TS-distribution of Chaoborus. The number of these smaller juvenile fish was so small compared with the number of Chaoborus that they did not seriously bias acoustic Chaoborus estimate. The correlation between the density of Chaoborus with small contamination of juvenile fish larvae from trawling and acoustic recording made with the 120 kHz echosounder was high (R2= 0.88), but the acoustic densities from trace counting appeared to underestimate Chaoborus abundance when the density was > 1.5 ind.m-3.